Identifying essential components of surgical care delivery through quality improvement: An updated surgical assessment tool. (October 2020) - Lin, Yihan; Raykar, Nakul P.; Saluja, Saurabh; Mukhopadhyay, Swagoto; Sharma, Sristi; Frett, Brigitte; Enumah, Sam; Iverson, Katherine R.; Johnson, Walter; Meara, John G.; Shrime, Mark G.
Abstract: Background: Surgical care is a cost-effective intervention with major public health impact. Yet, five billion people do not have access to surgical and anesthesia care. This overwhelming unmet need has generated a rising interest in scale-up of these services globally. The purpose of this research was to aggregate available guidelines and create a synthesized tool that could provide valuable information at the local, national, and international health system levels. Methods: A systematic review identified current documents cataloging elements for surgical care provision. Items with a reported frequency of >30% were included in the initial draft of the Surgical Assessment Tool. This underwent two cycles of Delphi-method expert opinion elicitation from providers working in low- and middle-income settings. Finally, the tool underwent vetting by the World Health Organization to create an expert-endorsed survey. Results: Fifteen surgical tools were identified, containing a total of 216 unique elements in the following domains: infrastructure (n = 152), service delivery (n = 49), and workforce (n = 15). The final tool consisted of 169 items in the following domains: infrastructure (n = 35), service delivery (n = 92), workforce (n = 20), information management (n = 10), and financing (n = 12). Conclusion: Informed planning is critical to ensure successful expansion of surgical services. Our analysis of current tools shows varying agreement on the essential components of surgical care delivery. This updated tool serves as a crucial method to systematically assess surgical systems as well as monitor, modify, and strengthen in a scalable fashion. Importantly, it has the potential to be used in all settings after adaptation to local context. Highlights: A variety of hospital surveys exist to assess surgery globally. Systematic review and expert consensus identified essential survey items. An updated, unified, comprehensive surgical assessment tool was created. The final tool is endorsed by the World Health Organization for international use.